Dimethyl Acetylenedicarboxylate: A Versatile Tool in Organic Synthesis - Neochoritis, Constantinos G.; Zarganes-Tzitzikas, Tryfon; Stephanidou-Stephanatou, Julia (Synthesis, 2014)
This review presents the recent progress in the chemistry of dimethyl acetylenedicarboxylate (DMAD). The interest in and applications of this powerful reagent with more than 135 years of history have greatly increased in the last 10 years, further proving its versatility. Undoubtedly, DMAD can be a multi-tool in the quest of molecular complexity and diversity. The extreme structural diversity of the products described in this review illustrates the powerful potential of DMAD as a building block in organic synthesis.1 Introduction2 Michael Reactions2.1 Sulfur as Nucleophile2.2 Nitrogen as Nucleophile2.3 Oxygen as Nucleophile2.4 Addition to Carbon–Carbon Double Bonds3 Cycloaddition Reactions3.1 Diels–Alder Reactions ([4+2] Cycloadditions)3.2 1,3-Dipolar Reactions ([3+2] Cycloadditions)3.3 [2+2] Cycloadditions3.4 [8+2] Cycloadditions4 DMAD and the Generation of Zwitterions; Multicomponent Reactions (MCRs)4.1 Phosphines and Derivatives4.2 Amines4.3 Isocyanides4.4 Carbenes4.5 Miscellaneous Reactions5 Conclusion
Keywords: DMAD; dimethyl acetylenedicarboxylate; Michael reactions; cycloadditions; multicomponent reactions